Barcoding, linear and nonlinear analysis of full‐day leg movements in infants with typical development and infants at risk of developmental disabilities: Cross‐sectional study. (15th March 2023) - Deng, Weiyang; Marmelat, Vivien; Vanderbilt, Douglas L.; Gennaro, Federico; Smith, Beth A.
Abstract: Traditional methods do not capture the multidimensional domains and dynamic nature of infant behavioral patterns. We aim to compare full‐day, in‐home leg movement data between infants with typical development (TD) and infants at risk of developmental disabilities (AR) using barcoding and nonlinear analysis. Eleven infants with TD (2–10 months) and nine infants AR (adjusted age: 2–14 months) wore a sensor on each ankle for 7 days. We calculated the standard deviation for linear variability and sample entropy (SampEn) of leg acceleration and angular velocity for nonlinear variability. Movements were also categorized into 16 barcoding states, and we calculated the SampEn and proportions of the barcoding. All variables were compared between the two groups using independent‐samples t ‐test or Mann‐Whitney U test. The AR group had larger linear variability compared to the TD group. SampEn was lower in the AR group compared to TD group for both acceleration and angular velocity. Two barcoding states' proportions were significantly different between the two groups. The results showed that nonlinear analysis and barcoding could be used to identify the difference of dynamic multidimensional movement patterns between infants AR and infants with TD. This information may help early diagnosis of developmental disabilities in the future.